LOCUS OF CONTROL SEBAGAI PEMODERASI PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA MANAJERIAL - asbi amin amin (Pusat P2M Politeknik Negeri Batam, 2020)
This research aimed to test the understanding of the budgetary participation and budget target clarity have effect to Manajerial Performance. Locus of Control able to moderate the effect of This research also to test the effect of risk preferences which acts as a moderating budgetary participation and budget target clarity to Manajerial Performance. This research took 54 respondents with a sampling technique is Judgement Sampling. Data collection was carried out through a questionnaire. The data analysis technique used in this study is Moderated Regression Analysis (MRA). Based on the results of the analysis it can be seen that the participation in budgeting and the clarity of budget targets has a positive and significant effect on managerial performance, then the Locus of control is not able to moderate the influence of participation in budgeting and the clarity of budget targets on managerial performance.